Manufacturing method and manufacturing device of carbon-coated optical fiber
Through real-time measurement and feedback adjustment technology of laser and X-rays, the problem of poor consistency of carbon film thickness and surface components in carbon coated fibers is solved, and efficient production and performance improvement of optical fibers is achieved.
Patent Information
- Application Number
- CN202411828708.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art cannot monitor and adjust the consistency of carbon film thickness and surface components in carbon coated optical fibers in real time, resulting in uneven carbon film thickness and poor surface components consistency, affecting the performance and application of optical fibers.
The carbon film thickness of the carbon coated bare fiber surface is measured in real time by using a laser beam, and the carbon coating process parameters are adjusted through the carbon film absorption energy difference feedback to achieve real-time online regulation of the carbon film thickness. At the same time, X-rays are used to measure the surface state of the carbon film, and process parameters are adjusted according to the feedback of the photoelectron egress kinetic energy to achieve real-time regulation of the surface state of the carbon film.
Real-time monitoring and adjustment of carbon film thickness and surface state is achieved, ensuring the thickness uniformity and surface components of carbon coated fibers, and improving the performance and application reliability of the fibers.
Smart Images

Figure CN119638216A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of special optical fiber manufacturing, and more specifically, relates to a method and device for manufacturing a carbon-coated optical fiber. Background Art
[0002] The existing carbon-coated optical fiber preparation scheme is mainly to draw the optical fiber preform rod by clamping it on the drawing tower. The surface of the optical fiber preform rod is carbon-coated by CVD (chemical vapor deposition) process. After the optical fiber is melted into a filament, it enters the carbon coating reaction chamber. The reaction gas hydrocarbon is introduced into the reaction chamber. In some production scenarios, chlorine-containing compounds are introduced. Through a series of dehydrogenation polymerization reactions, a carbon film coating with a specific coating thickness is achieved. After the carbon coating is completed, the optical fiber is cooled and enters a two-layer UV curing coating system. After the coating resin is selected and cured, the filament is collected at the end of the drawing tower to realize the carbon-coated optical fiber drawing process.
[0003] After the carbon-coated optical fiber is collected, it enters the strength screening process to determine the overall carbon-coated bare fiber strength performance and complete the strength performance test; sampling is required and the thickness of the carbon-coated carbon layer is tested using an electron microscope.
[0004] In the prior art, it is impossible to monitor the thickness of the carbon film produced in the carbon-coated optical fiber in real time; the carbon coating thickness needs to be tested by sampling and electron microscopy after the overall process is completed, and the thickness of the carbon film coated in the carbon coating process cannot be monitored in real time; for the microscopic conditions in the reaction chamber, such as the real-time reaction area changes on the bare optical fiber surface, the fluctuations in the drawing speed, and the uncontrollable deposition of carbon powder, the carbon film coating reaction may fluctuate, and the obtained carbon film may have uneven thickness and poor surface component consistency. Therefore, it is necessary to solve any of the problems of uneven thickness and poor surface component consistency of the carbon film obtained by the prior art.
[0005] In the prior art, the raw materials for carbon coating reactions are generally hydrocarbons and carbon-chlorine compounds. The ratio of hydrogen atoms to chlorine atoms in the hydrocarbons and carbon-chlorine compounds that participate in the reaction in real time is an important indicator of the strippability of the optical fiber. The prior art cannot monitor and adjust this ratio in real time. It is necessary to use sampling and optical fiber stripping equipment to determine the carbon film thickness and the strippability of the optical fiber after the overall process is completed. Therefore, the carbon-coated optical fiber that has completed the overall process has uneven stripping forces at different length ends of the optical fiber due to the uneven ratio of hydrogen atoms to chlorine atoms in the local reaction chamber. This seriously affects the performance indicators and practical applications of the carbon-coated optical fiber. Summary of the invention
[0006] In view of the defects of the prior art, the purpose of the present application is to provide a method and device for manufacturing carbon-coated optical fiber, aiming to solve the problem in the prior art that the carbon coating thickness must be tested after the entire process is completed, resulting in the inability to monitor the carbon coating film thickness in real time.
[0007] The present application provides a method for manufacturing a carbon-coated optical fiber, comprising the following steps:
[0008] preparing a bare optical fiber comprising a core and a cladding, and preparing a carbon coating layer on the bare optical fiber;
[0009] The carbon-coated bare fiber is irradiated with a directional and straight laser beam, and the thickness of the carbon film on the surface of the carbon-coated bare fiber is measured in real time through the laser light energy absorbed by the carbon-coated bare fiber. The carbon coating process parameters are adjusted according to the real-time measurement value feedback to achieve real-time online regulation of the carbon film thickness.
[0010] The carbon-coated bare fiber is subjected to resin coating and curing treatment to obtain a carbon-coated optical fiber with uniform carbon film thickness.
[0011] The present application uses the light energy difference coefficient to characterize different carbon film thicknesses mainly by utilizing the significant physical difference that the carbon coating absorbs light while the bare optical fiber can transmit light. By reasonably selecting the light wavelength, high-precision thickness testing accuracy can be achieved.
[0012] Furthermore, the thickness of the carbon film on the surface of the carbon-coated bare fiber is measured in real time by the laser light energy absorbed by the carbon-coated bare fiber, and the carbon coating process parameters are adjusted according to the real-time measurement value feedback to achieve real-time online regulation of the carbon film thickness. The specific steps are as follows:
[0013] Determine the light energy difference according to the carbon film thickness-carbon film absorption light energy mapping table and the laser light energy absorbed by the carbon coated bare fiber in real time;
[0014] Determine the change in hydrocarbon flow rate according to the ratio of the light energy difference to the ideal energy value in the mapping table;
[0015] Determining the feed amount of the carbon-hydrogen mixed raw material in the carbon coating process parameters according to the change amount and the initial value of the carbon-hydrogen flow rate;
[0016] The carbon film coating of the optical fiber is performed according to the feed amount of the hydrocarbon mixed raw material, thereby realizing feedback control of the carbon film thickness;
[0017] The carbon film thickness-carbon film absorbed light energy mapping table is constructed based on the ideal thickness and the ideal carbon film absorbed light energy.
[0018] Furthermore, the thickness of the carbon film can be determined according to the formula t=(lnL-lnLz) / 2k, where k is the carbon film absorption coefficient, Lz is the light energy difference, and L is the light intensity measured by the light intensity monitor.
[0019] The present application can use only one light path to irradiate the carbon-coated bare fiber to achieve the measurement of the carbon film thickness; it can also use two lights to irradiate the carbon-coated bare fiber from different directions to achieve non-interference testing from two vertical light paths, and obtain two light intensity values Lx and Ly; by calculating the carbon film uniformity λ=Lx / Ly, the uniformity of the carbon film coated on the bare optical fiber surface in two dimensions can be detected in real time; and the coating uniformity of the standard carbon layer in one dimension can be further detected.
[0020] Specifically, the two mutually perpendicular laser beams may be two laser beams with equal energy emitted by two laser light sources, or may be a total light source that is divided into two mutually perpendicular laser beams after beam expansion and beam splitting.
[0021] Furthermore, the following steps are also included before the carbon-coated bare fiber is resin coated:
[0022] The carbon-coated bare fiber is irradiated with X-rays, and the surface state of the carbon film is measured by the kinetic energy of photoelectron escape generated in real time on the surface of the carbon-coated bare fiber. The carbon coating process parameters are adjusted based on the real-time measurement value feedback to achieve real-time online regulation of the carbon film surface state.
[0023] Furthermore, the surface state of the carbon film is measured by the kinetic energy of photoelectrons emitted from the carbon-coated bare fiber surface in real time, and the carbon coating process parameters are adjusted according to the real-time measurement feedback to achieve real-time online regulation of the surface state of the carbon film. The specific steps are as follows:
[0024] Determine the difference in photoelectron escape kinetic energy according to the carbon film surface component-photoelectron escape kinetic energy mapping table and the photoelectron escape kinetic energy generated in real time by the carbon-coated bare fiber;
[0025] Determine the change in carbon-chlorine flow rate according to the ratio of the difference in photoelectron escape kinetic energy to the ideal photoelectron escape kinetic energy value in the mapping table;
[0026] Determine the feed amount of the carbon-chlorine mixed raw material according to the change amount and initial value of the carbon-chlorine flow rate;
[0027] The carbon film coating of the optical fiber is carried out according to the feeding amount of the carbon-chlorine mixed raw material, thereby realizing the feedback control of the surface components of the carbon film;
[0028] The carbon film surface component-photoelectron escape kinetic energy mapping table is constructed according to the ideal carbon layer surface component parameters and the ideal photoelectron escape kinetic energy value.
[0029] The present application uses the kinetic energy of photoelectron escape to measure the surface state of the carbon layer, analyzes the surface state of the carbon layer, adjusts the carbon coating process parameters based on the feedback of the analysis results, and controls the concentrations of carbon and chlorine raw materials in the carbon coating reaction chamber in real time, thereby achieving real-time regulation of the strippability of the carbon coating layer; the surface state of the carbon film is good, the bonding surface with the resin cured layer is uniform, and it is easier to strip; it can be used to meet the requirements of carbon-coated optical fibers in different applications.
[0030] The present application also provides a device for manufacturing a carbon-coated optical fiber, comprising a drawing device, a reaction chamber, a carbon coating and measurement feedback system, and a coating curing device; the drawing device is used to draw a preform rod into a bare optical fiber; raw materials required for the carbon coating process are introduced into the reaction chamber, and a carbon coating reaction occurs with the bare optical fiber in the reaction chamber; the carbon coating and measurement feedback system is used to provide a laser beam irradiated on the carbon-coated bare fiber, and the thickness of the carbon film on the surface of the carbon-coated bare fiber is measured in real time through the laser light energy absorbed by the carbon-coated bare fiber, and the carbon coating process parameters are adjusted according to the real-time measurement value feedback, so as to realize real-time online regulation of the carbon film thickness; the coating curing device is used to obtain a carbon-coated optical fiber after coating resin on the outside of the carbon coating layer and curing it.
[0031] Furthermore, the carbon coating and measurement feedback system includes: a thickness measuring unit, a thickness feedback unit, a hydrocarbon raw material gas cabinet, a carbon-chlorine raw material gas cabinet, a first flow controller, a second flow controller and a gas mixing device; the thickness measuring unit is used to measure the carbon film thickness on the surface of the carbon-coated bare fiber in real time through the laser light energy absorbed by the carbon-coated bare fiber; the thickness feedback unit is used to determine the light energy difference according to the carbon film thickness-carbon film absorption light energy mapping table and the laser light energy absorbed by the carbon-coated bare fiber in real time, and determine the electric quantity change of the hydrocarbon flow controller according to the ratio of the light energy difference to the ideal energy value in the mapping table; the first flow controller is used to determine the feed amount of the hydrocarbon mixed raw material according to the electric quantity change and the initial value of the hydrocarbon flow controller; the hydrocarbon raw material gas cabinet is used to store hydrocarbon raw materials; the carbon-chlorine raw material gas cabinet is used to store carbon-chlorine raw materials; the second flow controller is used to control the carbon-chlorine required for carbon coating to be fed at a set flow rate; the gas mixing device is used to pre-mix hydrocarbons and carbon-chlorine compounds before entering the reaction chamber to ensure that the raw materials are evenly mixed in the reaction chamber.
[0032] Furthermore, the thickness measuring unit is non-contact type and is arranged behind the reaction chamber, with the distance between the two being 150 mm to 650 mm.
[0033] Furthermore, the thickness measurement unit includes: a laser diode light source, a light intensity monitor, an optical filter and a photoelectric detector; the laser diode light source is used to emit a first laser beam with directionality and straightness and irradiate the carbon-coated bare fiber from one side; the light intensity monitor is used to monitor the real-time value and transmission stability of the light intensity of the first laser beam; the optical filter is arranged on the other side of the carbon-coated bare fiber, and is used to filter the influence of other light on the measurement process, and only pass the parallel light from the laser diode light source on the parallel path of the original laser; the photoelectric detector is used to receive the second laser beam emitted by the optical filter, and determine the real-time value of the light intensity of the second laser beam; the carbon film absorbs light energy by comparing the light energy of the second laser beam with the light energy of the first laser beam, and then the thickness of the carbon coating is determined according to the carbon film absorbs light energy.
[0034] Furthermore, the thickness measuring unit includes: a first laser diode light source, a first light intensity monitor, a first optical filter, a first photoelectric detector, a second laser diode light source, a second light intensity monitor, a second optical filter and a second photoelectric detector; the first laser diode light source emits a first laser beam with directivity and straightness and irradiates the carbon-coated bare fiber from a first direction; the second laser diode light source emits a second laser beam with directivity and straightness and irradiates the carbon-coated bare fiber from a second direction; the second direction is perpendicular to the first direction; the first light intensity monitor is used to monitor the real-time value and transmission stability of the light intensity of the first laser beam; the second light intensity monitor is used to monitor the real-time value and transmission stability of the light intensity of the second laser beam; the first optical filter and the first photoelectric detector are arranged in sequence in the first direction, and the first optical filter is used to filter the influence of other light on the measurement process, and only passes The parallel light from the first laser diode light source on the parallel path of the original laser is transmitted; the first photodetector is used to receive the third laser beam emitted by the first optical filter, and determine the real-time value of the light intensity of the third laser beam; the light energy absorbed by the first carbon film is obtained by comparing the light energy of the third laser beam with that of the first laser beam; the second optical filter and the second photodetector are sequentially arranged in the second direction, the second optical filter is used to filter the influence of other light on the measurement process, and only the parallel light from the second laser diode light source on the parallel path of the original laser is passed; the second photodetector is used to receive the fourth laser beam emitted by the second optical filter, and determine the real-time value of the light intensity of the fourth laser beam; the light energy absorbed by the second carbon film is obtained by comparing the light energy of the fourth laser beam with that of the second laser beam, and then the thickness of the carbon coating is determined according to the light energy absorbed by the first carbon film and the light energy absorbed by the second carbon film.
[0035] Furthermore, the thickness measuring unit includes: a laser diode light source, a laser beam expander, a laser beam splitter, a light intensity monitor, a first refractor, a second refractor, a first optical filter, a first photodetector, a second optical filter and a second photodetector; the laser diode light source is used to provide a laser beam with directivity and straightness; the laser beam expander is used to expand the laser beam; the laser beam splitter is used to split the expanded laser beam into two mutually perpendicular straight laser beams with equal energy, and monitor the real-time value of the light intensity and the transmission stability through the light intensity monitor; the above two laser beams are respectively vertically refracted through the first refractor and the second refractor The two laser beams are emitted, and the two laser beams remain perpendicular to each other after refraction; the two laser beams are emitted to the carbon-coated bare fiber according to the optical path and pass through to the other side of the incident optical path. On the other side, the two laser beams pass through the first optical filter and the second optical filter respectively. The main function of the optical filter is to filter the influence of other light on the measurement process, and only pass the parallel light from the laser diode light source on the parallel path of the original laser; the two perpendicular laser beams are received by the first photodetector and the second photodetector respectively, and the real-time value of the light intensity is determined; by comparing with the light energy after laser beam expansion, the carbon film absorbs the light energy; and then the coating thickness is determined according to the carbon film absorbs the light energy.
[0036] In an embodiment of the present application, the carbon coating and measurement feedback system is also used to provide X-rays to irradiate the carbon-coated bare fiber, measure the surface state of the carbon film through the kinetic energy of photoelectron escape generated in real time on the surface of the carbon-coated bare fiber, and adjust the carbon coating process parameters based on the real-time measurement value feedback to achieve real-time online regulation of the surface state of the carbon film.
[0037] Furthermore, the carbon coating and measurement feedback system also includes: a surface state measurement unit and a surface state feedback unit; the surface state measurement unit is used to measure the surface state of the carbon film; the surface state feedback unit compares the physical quantity used to characterize the surface state of the carbon film with the surface state process setting quantity, and transmits the comparison difference to the second flow controller.
[0038] Furthermore, the surface state measuring unit is non-contact type and is arranged after the thickness measuring unit, with the distance between the two being 100 mm to 400 mm.
[0039] Furthermore, the surface state measurement unit includes an X-ray source and an electron energy analyzer; the X-ray source is used to emit X-rays, and when the X-rays irradiate the surface of the carbon-coated bare fiber, they interact with the surface atoms, and when the photon energy is greater than the binding energy of the electrons outside the nucleus, photoelectrons can be excited; the electron energy analyzer is used to measure the energy distribution of the passing photoelectrons, and compare the photoelectron escape kinetic energy value with the surface state process setting value, and when the surface state of the carbon layer is consistent with the process, the photoelectron escape kinetic energy value used to characterize the surface state of the carbon layer is obtained.
[0040] More preferably, the gas mixing device may be circular, and the internal volume may match the feed rate of the raw material.
[0041] The present application also provides a carbon-coated optical fiber obtained based on the above-mentioned manufacturing method, comprising an optical fiber core layer, an optical fiber cladding, a carbon coating layer, a first solidified layer and a second solidified layer arranged in sequence.
[0042] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art:
[0043] (1) The light energy absorbed by the carbon film of the carbon-coated bare fiber is measured in real time, and the thickness of the carbon film represented by the measured resistance is determined through calibration and conversion, and the radial uniformity of the carbon film on the cross section of the carbon-coated bare fiber is preliminarily characterized; after obtaining the thickness characterization value, the numerical signal is connected to the thickness feedback control system. The thickness feedback system provides a feedback signal to the carbon-coated hydrocarbon raw material MFC in real time by comparing the difference between the measured value and the ideal calibration value, and corrects the hydrocarbon raw material gas supply flow rate in real time to ensure that the carbon film thickness is constant during the carbon coating process, and the overall carbon coating process can achieve long-term continuous wire drawing.
[0044] (2) The kinetic energy value of ionized photoelectrons on the surface of the optical fiber on which the carbon film is deposited is monitored in real time, and the surface state of the carbon film is determined through calibration and conversion; the numerical signal is connected to the surface state feedback control system, and the surface state feedback control system provides real-time feedback signals to the carbon-coated carbon-chlorine raw material MFC by comparing the difference between the measured value and the ideal calibration value, and corrects the carbon-chlorine raw material gas supply flow rate in real time to ensure that the surface state of the carbon film is constant during the carbon coating process and that the carbon-coated optical fiber is easy to strip within the entire drawing section. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a flow chart of the implementation of the method for manufacturing the carbon-coated optical fiber provided in the present application;
[0046] Figure 2 is a structural diagram of a device for manufacturing a carbon-coated optical fiber provided in the present application;
[0047] Figure 3 It is a structural schematic diagram of a first embodiment of a carbon layer measurement module in a carbon-coated optical fiber manufacturing device provided by the present application;
[0048] Figure 4 It is a structural schematic diagram of a second embodiment of a carbon layer measurement module in a carbon-coated optical fiber manufacturing device provided by the present application;
[0049] Figure 5(a) is a schematic diagram of the structure of a thickness measuring unit in a carbon-coated optical fiber manufacturing device provided in the first embodiment of the present application; (b) is a schematic diagram of the structure of a thickness measuring unit in a carbon-coated optical fiber manufacturing device provided in the second embodiment of the present application; (c) is a schematic diagram of the structure of a thickness measuring unit in a carbon-coated optical fiber manufacturing device provided in the third embodiment of the present application;
[0050] Figure 6 It is a schematic structural diagram of a surface state measurement unit in a carbon-coated optical fiber manufacturing device provided in the present application;
[0051] Figure 7 is a schematic diagram of the structure of a carbon-coated optical fiber obtained by using the carbon-coated optical fiber manufacturing device provided by the present application;
[0052] Figure 8 This is a comparison chart of the flow rates of hydrocarbon raw materials and carbon chlorine raw materials at various drawing length stages in the embodiments provided in this application.
[0053] In all the drawings, the same reference numerals are used to represent the same elements or structures, wherein: 1 is a wire drawing device, 2 is a reaction chamber, 3 is a carbon coating and measurement feedback system, 4 is a coating curing device, 5 is a caliper, 6 is a tractor, 7 is a wire collecting device, 31 is a thickness measuring unit, 32 is a thickness feedback unit, 33 is a hydrocarbon raw material gas tank, 34 is a carbon chlorine raw material gas tank, 35 is a first flow controller, 36 is a second flow controller, 37 is a gas mixing device, 38 is a surface state measurement unit, 39 is a gas mixing device, 40 is a surface state measurement unit, 41 is a surface state measurement unit, 42 is a surface state measurement unit, 43 is a surface state measurement unit, 44 is a surface state measurement unit, 45 is a surface state measurement unit, 46 is a surface state measurement unit, 47 is a surface state measurement unit, 48 is a surface state measurement unit, 49 is a surface state measurement unit, 50 is a surface state measurement unit, 51 is a surface state measurement unit, 52 is a surface state measurement unit, 53 is a surface state measurement unit, 54 is a surface state measurement unit, 55 is a surface state measurement unit, 56 is a surface state measurement unit, 57 is a surface state measurement unit, 58 is a surface state measurement unit, 59 is a surface state measurement unit, 60 is a surface state measurement unit, 61 is a surface state measurement unit, 62 is a surface state measurement unit, 63 is a surface state measurement unit, 64 is a surface state measurement unit, 65 is a surface state measurement unit, 66 is a surface state measurement unit, 67 is a surface state measurement unit, 68 is a surface state measurement unit, 69 is a surface state measurement unit, 70 is a surface state measurement unit, 71 is a surface state measurement unit, 72 is a surface state measurement unit, 73 is a surface state measurement unit 9 is a surface state feedback unit, 310 is a laser diode light source, 311 is a laser beam expander, 312 is a laser beam splitter, 313 is a light intensity monitor, 314 is a first refractor, 315 is a second refractor, 316 is a first optical filter, 317 is a first photodetector, 318 is a second optical filter, 319 is a second photodetector, 100 is an optical fiber core layer, 101 is an optical fiber cladding, 102 is an easily strippable carbon coating layer, 103 is a first solidified layer, and 104 is a second solidified layer. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0055] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the feature. In the description of the present application, "plurality" means two or more, unless otherwise clearly and specifically defined.
[0056] In addition, references throughout this specification to "one embodiment"; "one embodiment", "an example" or similar language indicate that a particular feature, structure, or characteristic described in conjunction with the embodiment is included in at least one embodiment of the present application. Thus, appearances of the phrase "in one embodiment"; "in one embodiment" and similar language throughout this specification may, but do not necessarily, all refer to the same embodiment.
[0057] In addition, the features, structures or features of the described application can be combined in one or more embodiments in any suitable manner. In the following description, a lot of specific details are provided, such as programming examples, software modules, user selections, network transactions, database queries, database structures, hardware modules, hardware circuits, hardware chips, etc., to provide a thorough understanding. Embodiments of the application. However, those skilled in the relevant art can recognize that the application can be implemented without one or more specific details, or using other methods, components, materials, etc. In other cases, well-known structures, materials or operations are not shown or described in detail to avoid confusing aspects of the application.
[0058] The carbon-coated optical fiber provided in the present application is a special optical fiber used in special environments such as aerospace and oil well fields. The carbon layer deposited on the bare fiber layer can effectively prevent moisture and hydrogen from affecting the mechanical strength and optical properties of the optical fiber.
[0059] In the carbon coating drawing process, the present application adds an online carbon film thickness measurement unit and an online surface state measurement unit between the carbon coating process and the resin coating process, monitors the physical quantities characterizing the carbon film thickness and surface state generated by the carbon coating process in real time, and feeds back the relevant data to the carbon layer coating system through the controller in real time, and accurately adjusts the flow of hydrogen atoms and chlorine atoms entering the carbon coating reaction chamber in real time by comparing with the calibrated ideal value and correcting the algorithm, so as to achieve the purpose of online feedback and correction of the carbon film thickness and the carbon film surface state; wherein the carbon film thickness determines the hydrogen loss sealing performance of the carbon-coated optical fiber; the carbon film surface state is directly related to the strippability of the carbon-coated optical fiber; the above-mentioned real-time feedback and corrected carbon coating drawing process method and corresponding device can realize the manufacture of long-length, high-strength and easy-to-strip carbon-coated optical fiber.
[0060] Figure 1 The implementation process of the method for manufacturing a carbon-coated optical fiber provided in an embodiment of the present application is shown. For the sake of convenience, only the part related to the present application is shown, which is described in detail as follows:
[0061] S1 prepares a bare optical fiber including a core and a cladding;
[0062] S2 preparing a carbon coating layer on the bare optical fiber;
[0063] S3 uses a directional and straight laser beam to illuminate the carbon-coated bare fiber, and measures the thickness of the carbon film on the surface of the carbon-coated bare fiber in real time through the laser light energy absorbed by the carbon-coated bare fiber;
[0064] S4 adjusts the carbon coating process parameters based on real-time measurement feedback to achieve real-time online control of carbon film thickness;
[0065] S7 performs resin coating and curing treatment on the carbon-coated bare fiber;
[0066] S8 performs a fiber-receiving process on the cured optical fiber to obtain a carbon-coated optical fiber with a uniform carbon film thickness.
[0067] In an embodiment of the present application, in order to accurately measure the thickness of the carbon film, after step S2 and before step S3, it also includes: detecting whether the temperature of the optical fiber is at an ideal temperature (i.e., 26° to 80°), if so, continuing with subsequent steps; if not, the optical fiber needs to be cooled.
[0068] In the embodiment of the present application, only one path of light can be used to irradiate the carbon-coated bare fiber to achieve the measurement of the carbon film thickness; or two paths of light can be used to irradiate the carbon-coated bare fiber from different directions. When the two laser beams with directivity and straightness are used to irradiate the carbon-coated bare fiber, the two laser beams are perpendicular to each other. Specifically, two laser light sources with equal energy can emit two laser beams respectively, or one laser light source can emit laser beams and then expand and split them into two mutually perpendicular laser beams to irradiate the carbon-coated bare fiber. Among them, the light source can use a light source with a wavelength range of 200nm to 550nm and sensitive absorption to the carbon element.
[0069] Among them, the thickness of the carbon film on the surface of the carbon-coated bare fiber is measured in real time by the laser light energy absorbed by the carbon-coated bare fiber, and the carbon coating process parameters are adjusted according to the real-time measurement value feedback to achieve real-time online regulation of the carbon film thickness. The specific steps are as follows:
[0070] Determine the light energy difference according to the carbon film thickness-carbon film absorption light energy mapping table and the laser light energy absorbed by the carbon coated bare fiber in real time;
[0071] Determine the change in hydrocarbon flow rate based on the ratio of the light energy difference to the ideal energy value in the mapping table;
[0072] Determining the feed amount of the carbon-hydrogen mixed raw material in the carbon coating process parameters according to the change amount and the initial value of the carbon-hydrogen flow rate;
[0073] The carbon film coating of the optical fiber is performed according to the feed amount of the hydrocarbon mixed raw material, thereby realizing feedback control of the carbon film thickness;
[0074] The film thickness-carbon film absorbed light energy mapping table is constructed based on the ideal thickness and the ideal carbon film absorbed light energy.
[0075] In the embodiment of the present application, the carbon film thickness t can be determined according to the formula t=(lnL-lnLz) / 2k, where k is the carbon film absorption coefficient, Lz is the light energy difference, and L is the light intensity measured by the light intensity monitor.
[0076] This application uses carbon film to absorb light energy to measure the thickness of the carbon film. Compared with the existing technology, it has the following technical advantages:
[0077] (1) The use of the light energy difference coefficient Lz / L to characterize the thickness of different carbon films is mainly based on the significant physical difference that the carbon coating absorbs light while the bare optical fiber can transmit light. By selecting a reasonable light wavelength, high-precision thickness testing accuracy can be achieved.
[0078] (2) The overall test system uses light absorption as the main physical principle and has a high tolerance to the environment. After the optical path is built and aligned, long-term online testing can be completed by simply ensuring the stability of the light source.
[0079] (3) This test method uses two light paths, and can complete non-interference testing from two perpendicular light paths to obtain two light intensity values Lx and Ly; by calculating the carbon film uniformity λ = Lx / Ly, the uniformity of the carbon film coated on the surface of the bare optical fiber in two dimensions can be detected in real time; and the coating uniformity of the standard carbon layer in one dimension can be further detected.
[0080] In step S4, the measured physical quantity characterizing the thickness of the carbon film is compared with the ideal thickness process setting, and the carbon coating hydrocarbon feed amount is controlled according to the comparison difference feedback, and the hydrocarbon feed amount is adjusted in real time, so as to achieve real-time control of the carbon film thickness by adjusting the carbon coating process parameters.
[0081] When anomalies cause the carbon film thickness to fluctuate, the existing technology is unable to correct the process through real-time adjustments and offset the thickness fluctuations caused by various microscopic conditions; however, the present application uses the carbon film to absorb light energy to measure the carbon film thickness, and processes the thickness. The carbon coating process parameters are adjusted based on the feedback of the processing results to achieve real-time regulation of the carbon film thickness.
[0082] In addition, in the prior art, the problem of fiber breakage and pulling stop caused by thickness fluctuation and carbon powder deposition interference results in a shorter carbon-coated optical fiber; the present application completes the carbon film absorption of light energy of the carbon-coated optical fiber through real-time measurement, converts it into carbon film thickness after calibration, and preliminarily characterizes the radial uniformity λ of the carbon film on the cross section of the carbon-coated bare optical fiber; after obtaining the thickness characterization value of the carbon film absorption of light energy, the numerical signal corresponding to the carbon film absorption of light energy is connected to the thickness feedback control system, and the thickness feedback system provides real-time feedback signal to the carbon-coated hydrocarbon raw material MFC by comparing the difference between the measured value and the ideal calibration value, and corrects the hydrocarbon raw material gas supply flow rate in real time to ensure that the carbon film thickness is constant during the carbon coating process, and the overall carbon coating process can achieve long-term continuous drawing.
[0083] In the embodiment of the present application, the following steps are also included before the optical fiber coated with the carbon layer is coated with resin:
[0084] S5 uses X-rays to irradiate carbon-coated bare fibers, and measures the surface state of the carbon film through the kinetic energy of photoelectrons generated in real time on the surface of the carbon-coated bare fibers; the energy value of the X-rays must meet (1-9)10 -19 J.
[0085] S6 adjusts the carbon coating process parameters based on real-time measurement feedback to achieve real-time online regulation of the carbon film surface state.
[0086] The surface state of the carbon film is measured by the kinetic energy of photoelectrons emitted in real time from the surface of the carbon-coated bare fiber, and the carbon coating process parameters are adjusted according to the real-time measurement feedback to achieve real-time online regulation of the surface state of the carbon film. The specific steps are as follows:
[0087] Determine the difference in photoelectron escape kinetic energy according to the carbon film surface component-photoelectron escape kinetic energy mapping table and the photoelectron escape kinetic energy generated in real time by the carbon-coated bare fiber;
[0088] Determine the change in carbon-chlorine flow rate according to the ratio of the difference in photoelectron escape kinetic energy to the ideal photoelectron escape kinetic energy value in the mapping table;
[0089] Determine the feed amount of the carbon-chlorine mixed raw material according to the change amount and initial value of the carbon-chlorine flow rate;
[0090] The carbon film coating of the optical fiber is carried out according to the feeding amount of the carbon-chlorine mixed raw material, thereby realizing the feedback control of the surface components of the carbon film;
[0091] The carbon film surface component-photoelectron escape kinetic energy mapping table is constructed based on the ideal carbon layer surface component parameters and the ideal photoelectron escape kinetic energy value.
[0092] In step S6, the measured surface state of the carbon layer is compared with a preset calibration value (due to the fixed linear relationship between the surface composition and the kinetic energy value of the ionized photoelectrons on the optical fiber surface, the atomic concentration at that location can be obtained by querying the X-ray photoelectron energy spectrum, which can characterize the surface density of the carbon atoms at that location, that is, the surface state). By adjusting the input flow rate of the carbon and chlorine raw material mass in real time, the feed amount of the carbon and chlorine raw materials entering can be changed, the concentration of the carbon and chlorine raw materials in the carbon coating reaction chamber can be controlled, and feedback control of the surface state of the carbon-coated carbon film can be achieved; the carbon and chlorine raw material feed amount can be adjusted by feedback, so that the surface state of the carbon layer can be stable and controllable in the long drawing section.
[0093] The existing technology requires the use of optical fiber stripping equipment to strip after the entire process is completed. If the carbon coating process causes uneven stripping strength at each end of the optical fiber due to uneven ratio of hydrogen atoms to chlorine atoms in the reaction chamber, the performance indicators will be seriously affected. The existing technology cannot monitor and adjust the ratio of hydrogen atoms to chlorine atoms in real time. However, the present application uses the kinetic energy of photoelectron escape to measure the surface state of the carbon layer; and processes the surface state of the carbon layer, adjusts the carbon coating process parameters according to the feedback of the processing results, and controls the concentration of carbon and chlorine raw materials in the carbon coating reaction chamber in real time, thereby achieving real-time regulation of the strippability of the carbon coating layer.
[0094] In summary, the method for manufacturing carbon-sealed coated optical fibers provided in the present application can meet the production needs of long-length carbon-sealed coated optical fibers; after completing the carbon coating process, the thickness of the carbon film in the carbon coating layer is uniform and stable over the entire length; the surface condition of the carbon film is good, the bonding surface with the resin cured layer is uniform, and it is easier to peel off; it can be used to meet the requirements for carbon-coated optical fibers in different applications.
[0095] Figure 2 The structure of the device for manufacturing a carbon-coated optical fiber provided in an embodiment of the present application is shown; for ease of description, only the part related to the present application is shown, which is described in detail as follows:
[0096] The manufacturing device of carbon-coated optical fiber includes a drawing device 1, a reaction chamber 2, a carbon coating and measurement feedback system 3, a coating curing device 4, a diameter gauge 5, a tractor 6 and a wire collecting device 7 which are connected in sequence, wherein the drawing device 1 is used to draw the preform into a bare optical fiber (uncoated); the raw materials required for the carbon coating process are introduced into the reaction chamber 2, and a carbon coating reaction occurs with the bare optical fiber in the reaction chamber 2; the carbon coating and measurement feedback system 3 is used to provide a laser beam irradiated on the carbon-coated bare fiber, and the thickness of the carbon film on the surface of the carbon-coated bare fiber is measured in real time by the laser light energy absorbed by the carbon-coated bare fiber, and the carbon coating process parameters are adjusted according to the real-time measurement value feedback to realize real-time online regulation of the carbon film thickness; the coating curing device 4 is used to coat the resin (acrylic resin) on the outside of the carbon coating layer and cure it to ensure the basic mechanical strength and other properties of the optical fiber; the diameter gauge 5 is used to measure the overall diameter of the optical fiber at this time; the tractor 6 is used to pull the optical fiber in the overall drawing process; the wire collecting device 7 is used to store the continuously drawn optical fiber through rotational motion.
[0097] The structure of the first embodiment of the carbon coating and measurement feedback system 3 is as follows: Figure 3As shown, it includes a thickness measuring unit 31, a thickness feedback unit 32, a hydrocarbon raw material gas cabinet 33, a carbon chlorine raw material gas cabinet 34, a first flow controller 35, a second flow controller 36 and a gas mixing device 37, wherein the thickness measuring unit 31 is used to measure the carbon film thickness on the surface of the carbon-coated bare fiber in real time through the laser light energy absorbed by the carbon-coated bare fiber; the thickness feedback unit 32 is used to determine the light energy difference according to the carbon film thickness-carbon film absorption light energy mapping table and the laser light energy absorbed by the carbon-coated bare fiber in real time, and determine the electrical quantity change of the hydrocarbon flow controller according to the ratio of the light energy difference to the ideal energy value in the mapping table; the first flow controller 35 is used to determine the electrical quantity change of the hydrocarbon mixing raw material according to the hydrocarbon flow controller electrical quantity change and the initial value The feed amount of the material; thereby the hydrocarbon feed amount is feedback-adjusted in real time, and the adjustment amount is determined by the contrast difference measured in real time by the thickness feedback unit 32; the hydrocarbon raw material gas cabinet 33 is used to store hydrocarbon raw materials; the carbon-chlorine raw material gas cabinet 34 is used to store carbon-chlorine raw materials; the second flow controller 36 is used to control the carbon-chlorine required for carbon coating to feed the carbon-chlorine compound according to the required reference thickness of the carbon-chlorine compound; the gas mixing device 37 is used to pre-mix hydrocarbons and carbon-chlorine compounds before entering the reaction chamber 2 to ensure that the raw materials are evenly mixed in the reaction chamber; to ensure the above-mentioned technical effects, the device can be designed to be circular, the internal volume matches the raw material feed speed, and a heating device is added to the outside of the device to accelerate the mixing process.
[0098] In the present application, the first flow controller 35 and the second flow controller 36 have the same working principle, specifically: the flow controller divides the incoming fluid into two streams according to a fixed ratio, one of which passes through the temperature sensor and the other passes through the main channel normally, and then measures the temperature difference between the two streams; since each gas molecule can absorb a specific heat value, the temperature difference can characterize the number of fluid molecules passing through; then the temperature difference signal is transmitted to the analog-to-digital sensor, and the analog-to-digital sensor outputs a voltage signal, and the specific flow rate is determined by the voltage signal value and the specific heat absorption coefficient of the gas molecule. The molecular weight of the fluid passing through the mass flow controller, that is, the flow rate of the fluid, is determined by setting the voltage signal value.
[0099] In order to ensure that the internal volume of the gas mixing device 37 matches the raw material feeding speed, the ideal mixing time is about 10 minutes to 50 minutes, that is, the internal volume needs to be able to accommodate the amount of raw materials entering within this time.
[0100] As an embodiment of the present application, the carbon layer thickness measurement unit 31 is non-contact and is arranged behind the carbon coating reaction chamber 2. The distance between the two needs to leave enough distance for the optical fiber to cool down. The distance value can be set between 150mm and 650mm; to ensure that the bare optical fiber has basically completed the cooling after the carbon coating process is completed, the thickness measurement can be performed online.
[0101] In an embodiment of the present application, the carbon coating and measurement feedback system 3 is also used to provide X-rays to irradiate the carbon-coated bare fiber, measure the surface state of the carbon film through the kinetic energy of photoelectron escape generated in real time on the surface of the carbon-coated bare fiber, and adjust the carbon coating process parameters according to the real-time measurement value feedback, so as to realize real-time online regulation and control of the surface state of the carbon film.
[0102] The structure of the second embodiment of the carbon coating and measurement feedback system 3 is as follows: Figure 4 As shown, the second embodiment includes a thickness measuring unit 31, a thickness feedback unit 32, a hydrocarbon raw material gas cabinet 33, a carbon chlorine raw material gas cabinet 34, a first flow controller 35, a second flow controller 36, a gas mixing device 37, a surface state measuring unit 38 and a surface state feedback unit 39; compared with the first embodiment, the second embodiment adds a surface state measuring unit 38 and a surface state feedback unit 39; the surface state measuring unit 38 is arranged after the thickness measuring unit 31, and is used to measure the surface state of the carbon film; the surface state feedback unit 39 compares the physical quantity used to characterize the surface state of the carbon film with the surface state process setting quantity, and transmits the comparison difference to the second flow controller 36; in addition to controlling the carbon and chlorine compounds required for carbon coating to be fed according to the surface state process setting quantity, the second flow controller 36 also adjusts the feed amount of carbon and chlorine compounds through feedback control in real time, and the adjustment amount is determined by the comparison difference measured in real time by the surface state feedback unit 39.
[0103] In the embodiment of the present application, the carbon layer surface state measurement unit 38 is non-contact and can be arranged after the carbon layer thickness measurement unit 31. The distance between the two needs to leave enough distance for the optical fiber to cool down; the distance value is preferably between 100mm and 400mm, so as to ensure that the temperature is reduced to meet the requirements, so that there is no interference in the measurement process of both parties.
[0104] As a first embodiment of the thickness measuring unit 31 in the present application, Figure 5 As shown in (a), the thickness measuring unit 31 includes: a laser diode light source, a light intensity monitor, an optical filter and a photodetector; the laser diode light source is used to emit a first laser beam with directivity and straightness and irradiate the carbon-coated bare fiber from one side; the light intensity monitor is used to monitor the real-time value and transmission stability of the light intensity of the first laser beam; the optical filter is arranged on the other side of the carbon-coated bare fiber, and is used to filter the influence of other light on the measurement process, and only pass the parallel light from the laser diode light source on the parallel path of the original laser; the photodetector is used to receive the second laser beam emitted by the optical filter, and determine the real-time value of the light intensity of the second laser beam; the carbon film absorbs light energy by comparing the light energy of the second laser beam with the light energy of the first laser beam, and then the thickness of the carbon coating is determined according to the carbon film absorbs light energy.
[0105] As a second embodiment of the thickness measuring unit 31 in the present application, Figure 5 As shown in (b), the thickness measuring unit 31 includes: a first laser diode light source, a first light intensity monitor, a first optical filter, a first photodetector, a second laser diode light source, a second light intensity monitor, a second optical filter and a second photodetector; the first laser diode light source emits a first laser beam with directivity and straightness and irradiates the carbon-coated bare fiber from a first direction; the second laser diode light source emits a second laser beam with directivity and straightness and irradiates the carbon-coated bare fiber from a second direction; the second direction is perpendicular to the first direction; the first light intensity monitor is used to monitor the real-time value and transmission stability of the light intensity of the first laser beam; the second light intensity monitor is used to monitor the real-time value and transmission stability of the light intensity of the second laser beam; the first optical filter and the first photodetector are sequentially arranged in the first direction, and the first optical filter is used to filter the influence of other light on the measurement process, Only the parallel light from the first laser diode light source on the parallel path of the original laser is passed; the first photodetector is used to receive the third laser beam emitted by the first optical filter, and determine the real-time value of the light intensity of the third laser beam; the light energy absorbed by the first carbon film is obtained by comparing the light energy of the third laser beam with that of the first laser beam; the second optical filter and the second photodetector are sequentially arranged in the second direction, the second optical filter is used to filter the influence of other light on the measurement process, and only the parallel light from the second laser diode light source on the parallel path of the original laser is passed; the second photodetector is used to receive the fourth laser beam emitted by the second optical filter, and determine the real-time value of the light intensity of the fourth laser beam; the light energy absorbed by the second carbon film is obtained by comparing the light energy of the fourth laser beam with that of the second laser beam, and then the thickness of the carbon coating is determined according to the light energy absorbed by the first carbon film and the light energy absorbed by the second carbon film.
[0106] As a third embodiment of the thickness measuring unit 31 in the present application, a thickness measuring unit 31 is set at the cross section of the carbon-coated bare fiber. The structure of the thickness measuring unit 31 is as follows: Figure 5As shown in (c), it includes a laser diode light source 310, a laser beam expander 311, a laser beam splitter 312, a light intensity monitor 313, a first refractor 314, a second refractor 315, a first optical filter 316, a first photodetector 317, a second optical filter 318 and a second photodetector 319, wherein the laser diode light source 310 is used to provide a laser beam with directivity and straightness, and its wavelength is within the sensitive absorption wavelength of carbon element; the laser beam is expanded by the laser beam expander 311, and the laser beam reaches the laser beam splitter 312 after the expansion is completed. The laser beam splitter 312 splits the laser into two mutually perpendicular and equal energy straight laser beams, and the real-time value of the light intensity and the transmission stability are monitored by the light intensity monitor 313; the above two laser beams The two laser beams are respectively refracted vertically by the first refractor 314 and the second refractor 315, and remain perpendicular to each other after refraction; the two laser beams are emitted to the carbon-coated bare fiber according to the optical path and pass through to the other side of the incident optical path, and on the other side, the two laser beams are respectively passed through the first optical filter 316 and the second optical filter 318, and the main function of the optical filter is to filter out the influence of other interfering light on the measurement process, and only pass the parallel light from 310 on the parallel path of the original laser; the two vertical laser beams are respectively received by the first photodetector 317 and the second photodetector 319, and the real-time value of the light intensity after the carbon film absorbs is determined; by comparing with the incident light energy measured by the light intensity monitor 313, the carbon film absorbs the light energy, and then the coating thickness is determined according to the carbon film absorbs the light energy.
[0107] In the above process, after the laser light source is expanded, split and refracted, the light intensity after expansion and before splitting is measured by the light intensity monitor 313 as L, and two parallel lights that do not interfere with each other pass through the bare optical fiber coated with carbon on the surface. After being attenuated by the carbon film once, the parallel light passes through the bare optical fiber glass and then attenuates by the carbon film again on the other side. Finally, the parallel light passes through the bare optical fiber. On the other side of the optical path, it is assumed that the first photodetector 317 and the second photodetector 319 measure the light intensity values as Lx and Ly respectively; because the optical fiber material has very little attenuation for the parallel light path, the attenuation can be basically ignored compared with the attenuation caused by the carbon film; therefore, the specific value of the light energy difference Lz after attenuation formed by passing through the carbon film twice is Lz≈L-(Lx+Ly); and the size of Lz is proportional to L and has an approximately exponential relationship with the carbon film thickness t; therefore: Lz=L*e -2kt ; Where k is the carbon film absorption coefficient.
[0108] The thicker the carbon film is, the higher the laser transmittance is; therefore, the carbon film thickness can be obtained by conversion: t = (lnL-lnLz) / 2k.
[0109] In addition to the value t that directly represents the carbon film thickness, the light energy difference coefficient μ = Lz / L and the carbon film uniformity λ = Lx / Ly can be obtained through the above measurement optical path. The light energy difference coefficient μ is used to represent the influence of different carbon film thicknesses on light intensity, and the carbon film uniformity λ is used to represent whether the carbon film thickness in two typical radial directions is uniform.
[0110] The testing method provided by the present application mainly includes the following advantages: (a) The use of light energy difference coefficient to characterize different carbon film thicknesses mainly utilizes the significant physical difference that the carbon coating absorbs light while the bare optical fiber can transmit light. By selecting a reasonable light wavelength (wavelength between 200nm and 550nm), high-precision thickness testing accuracy can be achieved; (b) The overall testing system uses light absorption as the main physical principle and has high environmental tolerance; and after completing the optical path construction and alignment, it is only necessary to ensure the stability of the light source to complete long-term online testing; (c) This testing method can use two light paths, and non-interference tests can be completed from two vertical light paths to obtain two light intensity values Lx and Ly; by calculating the carbon film uniformity λ=Lx / Ly, the uniformity of the carbon film coated on the bare optical fiber surface in two dimensions can be detected in real time; and the coating uniformity of the standard carbon layer in one more dimension can be measured.
[0111] In the embodiment of the present application, the structure of the surface state measuring unit 38 is as follows: Figure 6 As shown, it includes an X-ray source 381 and an electron energy analyzer 382; the surface state feedback control unit uses the X-ray source 381 with a fixed wavelength to emit X-rays (wherein the energy value of the X-rays must meet (1-9) 10 -19 J), irradiate the surface of the carbon-coated bare fiber, and the X-rays interact with the surface atoms (specifically, the X-rays are emitted to the surface of the carbon film, and the photons are absorbed by the electrons in the orbits of the carbon atoms in the carbon film, causing the electrons to break free from the constraints of the nucleus and be emitted from the inside of the atom with a certain kinetic energy to become free photoelectrons). When the photon energy is greater than the binding energy of the electrons outside the nucleus, the inner electrons can be excited, and the excited photoelectrons enter the electron energy analyzer 382. The electron energy analyzer 382 is used to measure the energy distribution of the photoelectrons passing through during this time (since the electron energy analyzer is a channel type, it can measure the energy carried by the excited electrons in real time. Since the X-rays are continuously emitted, the electrons continue to pass through in a time sequence, so the photoelectron energy distribution during this time can be obtained). The kinetic energy of the photoelectrons emitted by each atom has a single characteristic; a range of photoelectron escape kinetic energy values corresponding to the ideal surface state of the carbon-coated optical fiber needs to be set in the surface state feedback control unit. The value range is 4.8 to 5.2 (unit 10 -19 J). By comparing the measured photoelectron escape kinetic energy value with the above ideal value, it can be concluded whether the surface state of the carbon layer is consistent with the process.
[0112] As an embodiment of the present application, since the energy of the photoelectrons emitted from the surface of the carbon film after X-ray irradiation has a linear relationship with the concentration of the atom in the surface of the carbon film, a graph is needed for spectral comparison. The surface state measurement unit 38 also includes an electron detector 383 and a data display 384. Since the energy of the electron flow analyzed in the electron energy analyzer 382 is weak, the excited photoelectrons immediately enter the electron detector 383. The electron detector 383 is used to form electron multiplication, improve data collection capabilities and count the number of electrons passing through the entire channel. The data display 384 is used to collect the number of electrons and energy values passing through the detector 383 to form a database for analyzing and real-time monitoring of the surface state of the entire carbon coating process.
[0113] Compared with the roughness surface morphology measurement to determine the quality of the carbon film, the main advantages of this test method adopted in this application are: (a) The main advantage of using the photoelectron escape kinetic energy to characterize the surface state of the carbon layer is that X-rays can accurately determine the surface state of the carbon layer within 10nm through photoelectron energy spectrum measurement, and the resolution and sensitivity are much greater than the traditional AFM measurement method. The process curve after data processing can monitor the stability of the overall wire drawing process at a higher precision level. (b) The test source of the photoelectron escape kinetic energy is an X-ray emitter, and the distance between the emitter and the carbon-coated bare fiber can be adjusted according to the concentration of the X-rays; compared with the requirement of the nanometer-level distance between the probe and the optical fiber in the traditional AFM measurement, the physical distance of the emitter is several orders of magnitude farther, with low environmental restrictions and lower precision requirements for equipment adjustment.
[0114] The working process of the carbon-coated optical fiber manufacturing device provided in the embodiment of the present application is as follows:
[0115] The quartz optical fiber preform is melted at high temperature in the drawing device 1, and a bare optical fiber is formed under a certain tension. The bare optical fiber directly enters the reaction chamber 2 at high temperature. The raw materials required for the carbon coating process enter the reaction chamber 2 from the hydrocarbon raw material gas cabinet 33 and the carbon chlorine raw material gas cabinet 34. In order to ensure the stability of the pressure and flow of the raw materials, the hydrocarbon raw material enters the first flow controller 35 from the hydrocarbon raw material gas cabinet 33, and the flow is controlled by the first flow controller 35. The carbon chlorine raw material enters the second flow controller 36 from the carbon chlorine raw material gas cabinet 34, and the flow is controlled by the second flow controller 36. The two controlled airflows first converge into the gas mixing device 37, and after the gas mixing device 37 enters the pre-mixing, the carbon coating reaction raw material enters the gas inlet of the reaction chamber 2 from the gas mixing device 37; the reaction gas enters the reaction chamber from the gas inlet.
[0116] The optical fiber pulled by the traction device 6 is drawn along the axis, and the bare optical fiber drawn from the high-temperature drawing device 1 directly enters the carbon-coated reaction chamber 2 and is pulled downward through the reaction chamber 2; in the reaction chamber 2, the bare optical fiber is mixed with the reaction gas entering from the air inlet, and the high temperature of the bare optical fiber is used to realize the cracking of the reaction raw materials without adopting other heating measures; thus completing the process of forming a carbon film on the surface of the bare fiber.
[0117] The carbon-coated bare fiber that has completed the carbon coating process is further pulled downward by the traction device 6, and the carbon-coated bare fiber passes through the carbon layer thickness measuring unit 31; the carbon-coated bare fiber passes through the carbon layer thickness measuring unit 31, and the light energy loss passing through the carbon-coated bare fiber is measured by the non-contact optical principle, and the carbon film absorbs light energy through physical calculation, and the carbon film absorbs light energy through the signal to the thickness feedback unit 32, and is compared with the preset calibration value in the thickness feedback unit 32 (that is, the light energy transmission loss corresponding to the ideal carbon film thickness value), and control feedback is performed according to the comparison value, and the input flow of the first flow controller 35 of the hydrocarbon raw material mass is adjusted in real time to achieve the change of the hydrocarbon raw material feed amount entering the gas mixing device 37, to achieve the concentration control of the hydrocarbon raw material in the carbon coating reaction chamber 2, and to achieve feedback control of the carbon coating carbon film thickness; so as to achieve the purpose of stable coating of the carbon layer thickness by adjusting the hydrocarbon raw material feed amount through feedback.
[0118] The carbon-coated bare fiber after thickness measurement is further pulled downward by the traction device 6, and the carbon-coated bare fiber passes through the surface state measurement unit 38; the carbon-coated bare fiber passes through the surface state measurement unit 38, and the surface state measurement unit 38 adopts the principle of X-ray photoelectron testing (XPS), and measures the kinetic energy value of ionization photoelectrons on the surface of the carbon-coated bare fiber by an XPS non-contact probe, and the power value is connected to the surface state feedback unit 39 through a signal, and is compared with the preset calibration value in the surface state feedback unit 39 (that is, the kinetic energy value of ionization photoelectrons on the surface of the carbon-coated bare fiber corresponding to the ideal easy-to-peel carbon-coated bare fiber). By adjusting the input flow rate of the carbon-chlorine raw material mass in the second flow controller 36 in real time, the feed amount of carbon-chlorine raw materials entering the gas mixing device 37 is changed, the concentration of carbon-chlorine raw materials in the carbon coating reaction chamber is controlled, and feedback control of the surface state of the carbon-coated carbon film is achieved; the carbon-chlorine raw material feed amount is adjusted by feedback, so that the surface state roughness value of the carbon layer is stable and controllable in the long drawing section.
[0119] Through the above process, the carbon film thickness and surface state index of the carbon-coated bare fiber are controlled by online real-time feedback; the carbon-coated bare fiber passing through the surface state measurement unit 38 continues to be pulled downward by the puller 6; after two layers of UV curing coating, the first layer coating cup 5, the first layer curing furnace 6, the inner layer is a low modulus resin coating; the second layer coating cup 7; the second layer curing furnace 8, the outer layer is a high modulus resin material; the two layers of UV-cured coated optical fiber pass through the diameter gauge 5, the diameter gauge 5 feeds back to the puller 6 through the control signal, so that the optical fiber diameter is kept within the required range; the carbon-coated bare fiber that has completed the overall traction is completed by the wire collection device 7.
[0120] The carbon coated bare fiber structure is prepared by this application as Figure 7 As shown, the carbon-coated bare fiber includes an optical fiber core layer 100, an optical fiber cladding 101, an easily strippable carbon coating layer 102, a first solidified layer 103 and a second solidified layer 104. Compared with the prior art, the carbon-coated optical fiber prepared by the present production method and the production device can achieve stable and continuous carbon coating of the bare optical fiber, and achieve continuous drawing of long-length optical fibers, which can match the highly enclosed scenes where the continuous segment length and hydrogen damage resistance of the optical fiber are required to be high in special environments such as oil wells and the seabed, and optical fiber fault repair cannot be performed; especially for communication scenarios such as deep-sea oil wells and offshore seabeds, the communication segment span reaches 30 km or more, and the optical fiber cable is laid in an environment such as oil and seawater, and the continuous segment length of the optical fiber also reaches more than 30 km. The optical fiber produced by the present device can meet such requirements.
[0121] In addition, for application scenarios such as photoelectric conversion, in addition to high requirements for hydrogen loss capacity indicators, optical fibers also need to be stripped multiple times for fusion splicing between devices. Therefore, the requirements for the easy stripping index of the stripping layer are relatively high. For carbon-coated bare fibers, the outer layer of the carbon coating and the inner layer of the first solidified layer are the stripping layers. The carbon-coated optical fiber produced by this device has the characteristics of continuous easy stripping (that is, the stripping force is between 1N and 2N), and there are no special requirements for the stripping point and the stripping section length, and can be used in various scenarios of complex photoelectric conversion scenarios.
[0122] In this application, after the bare optical fiber has been carbon-coated, two layers of resin UV curing are required; the first layer of resin is a low modulus resin, and the second layer of resin is a high modulus resin. For the overall resin modulus, the selection of the modulus needs to match the bending ability of each material layer of the overall optical fiber. Compared with traditional optical fibers, the optical fiber material layer has an additional carbon film layer, and material layers of different thicknesses also have different bending abilities. For this part of the matching, the main method is to use material layers of different thicknesses to conduct optical fiber drawing tests (such as Figure 7For different application scenarios, when high bending performance and hydrogen loss performance are required in general carbon-coated optical fibers, such as data centers with more photoelectric conversion fusion splicing, the carbon-coated carbon film thickness is generally 30nm~60nm. At this time, the first layer of resin modulus selects low modulus resin, and the second layer of resin modulus selects high modulus resin. The bending capabilities of each material layer are well matched, which can better achieve high-stability applications in data centers; for carbon-coated optical fibers with low bending performance requirements and higher hydrogen loss performance requirements, such as oil wells, oceans and other long-distance linear transmission scenarios, the carbon coating thickness is generally 60nm~100nm. At this time, the first layer of resin modulus selects low modulus resin, and the second layer of resin modulus selects high modulus resin. The bending capabilities of each material layer are well matched, which can better achieve high-stability applications in the above special environments.
[0123] In order to further illustrate the manufacturing method and manufacturing device of the carbon-coated optical fiber provided in the present application, further illustrate the effectiveness of the carbon film thickness measurement feedback and the surface component measurement feedback; as well as the influence of the first layer resin modulus and the initial flow value of the carbon-chlorine raw material on the easy-to-strip performance; now it is described in detail as follows in combination with specific embodiments:.
[0124] Example 1: The carbon-coated optical fiber drawing device shown in the present application is used, and a standard optical fiber graphite furnace is used. The outer diameter of the bare optical fiber is controlled to be 125um. After the carbon coating process module, the carbon coating thickness measurement and feedback unit and the carbon film surface state measurement and feedback unit are closed, and the outer diameter of the optical fiber after double-layer resin curing coating is controlled to be 250um; the parameters of the overall drawing process are as follows; in this example, after drawing to 10km, the carbon coating reaction chamber begins to have obvious deposited carbon powder; the overall drawing to 12Km has a tower break and the coating is interrupted; 30km of carbon-coated optical fiber in the drawing disk is screened, and the entire disk is screened; the optical fiber is uniformly sampled offline for thickness electron microscope test and stripping force test to obtain the following results:
[0125]
[0126] In Example 1, a carbon coating process was used, and the carbon coating thickness measurement and feedback unit and the carbon film surface state measurement and feedback unit involved in the present application were not turned on; the overall wire drawing process became unstable at 10 km, and after offline testing, it was found that the thickness fluctuated greatly and the peeling force was also large;
[0127] Example 2: The carbon-coated optical fiber drawing device shown in the present application is used, a standard optical fiber graphite furnace is used, the outer diameter of the bare optical fiber is controlled to be 125um, and after the carbon coating process module, the carbon coating thickness measurement and feedback unit is turned on, the carbon film surface state measurement and feedback unit is turned off, and the outer diameter of the optical fiber after double-layer resin curing coating is controlled to be 250um; the parameters of the overall drawing process are as shown in the following table; in this example, after drawing to 8km, obvious carbon powder deposition begins to appear in the carbon coating reaction chamber and gradually stabilizes; the overall drawing is interrupted at 50km, and the coating is interrupted; 30km of carbon-coated optical fiber in the drawing disk is screened, and the entire disk is screened; the optical fiber is uniformly sampled offline for thickness electron microscope test and stripping force test to obtain the following results:
[0128]
[0129] Compared with Example 1, in Example 2, the carbon coating thickness measurement unit is turned on, and other parameters remain unchanged; the overall drawing length is greatly increased, and the consistency of the carbon film thickness is greatly improved.
[0130] Example 3: The carbon-coated optical fiber drawing device shown in the present application is used, and a standard optical fiber graphite furnace is used. The outer diameter of the bare optical fiber is controlled to be 125um. After the carbon coating process module, the carbon coating thickness measurement and feedback unit and the carbon film surface state measurement and feedback unit are turned on. The outer diameter of the optical fiber after double-layer resin curing coating is controlled to be 250um; the parameters of the overall drawing process are as shown in the following table; in this example, after drawing to 9km, the carbon coating reaction chamber begins to have obvious deposited carbon powder; the overall drawing to 49Km has a tower break and the coating is interrupted; the 30km carbon-coated optical fiber in the drawing disk is screened, and the screening is completed in the entire disk; the optical fiber is uniformly sampled offline for thickness electron microscope test and stripping force test to obtain the following results:
[0131]
[0132]
[0133] In the third embodiment, Figure 8 The flow rate of hydrocarbon raw materials and carbon chlorine raw materials at each drawing length stage is compared. Figure 8 From the data shown, it can be seen that as the drawing process continues, the feed amounts of hydrocarbon raw materials and carbon chlorine raw materials are controlled and corrected in real time through real-time feedback of measurement data from the carbon film thickness tester and the carbon layer surface state micrometer; the offline measurement results show that the carbon layer coating thickness is uniform over the entire drawing length through feed amount control; the peeling force index corresponding to the surface state is adjusted by adjusting the flow rate of carbon chlorine raw materials, and the results are good.
[0134] In general, the carbon-coated optical fiber production method and production device can effectively avoid the adverse effects of ineffective carbon deposition reactions during the carbon coating process by accurately measuring the thickness and surface state of the carbon-coated bare fiber in real time and providing real-time feedback to the process parameters, thereby achieving the preparation of long and easily strippable carbon-coated optical fibers.
[0135] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A method for manufacturing a carbon-coated optical fiber, characterized in that: The steps include: Preparing a bare optical fiber comprising a core and a cladding, and preparing a carbon coating layer on the bare optical fiber; The carbon-coated bare fiber is irradiated with a directional and straight laser beam, and the thickness of the carbon film on the surface of the carbon-coated bare fiber is measured in real time through the laser light energy absorbed by the carbon-coated bare fiber. The carbon coating process parameters are adjusted according to the real-time measurement value feedback to achieve real-time online regulation of the carbon film thickness. The carbon-coated bare fiber is subjected to resin coating and curing treatment to obtain a carbon-coated optical fiber with uniform carbon film thickness.
2. The method according to claim 1, characterized in that: A laser beam is used to irradiate the carbon-coated bare fiber; or two laser beams perpendicular to each other are used to irradiate the carbon-coated bare fiber.
3. The method according to claim 1, characterized in that: The steps of measuring the thickness of the carbon film on the surface of the carbon-coated bare fiber in real time by using the laser light energy absorbed by the carbon-coated bare fiber, and adjusting the carbon coating process parameters according to the real-time measurement value feedback to achieve real-time online regulation of the carbon film thickness are specifically as follows: Determine the light energy difference according to the carbon film thickness-carbon film absorption light energy mapping table and the laser light energy absorbed by the carbon coated bare fiber in real time; Determine the change in hydrocarbon flow rate according to the ratio of the light energy difference to the ideal energy value in the mapping table; Determining the feed amount of the carbon-hydrogen mixed raw material in the carbon coating process parameters according to the change amount and the initial value of the carbon-hydrogen flow rate; The carbon film coating of the optical fiber is performed according to the feed amount of the hydrocarbon mixed raw material, thereby realizing feedback control of the carbon film thickness; The carbon film thickness-carbon film absorbed light energy mapping table is constructed according to the ideal thickness and the ideal carbon film absorbed light energy.
4. The method according to claim 1, characterized in that: The following steps are also included before the carbon coated bare fiber is resin coated: The carbon-coated bare fiber is irradiated with X-rays, and the surface state of the carbon film is measured by the kinetic energy of photoelectron escape generated in real time on the surface of the carbon-coated bare fiber. The carbon coating process parameters are adjusted based on the real-time measurement value feedback to achieve real-time online regulation of the carbon film surface state.
5. The method according to claim 4, characterized in that: The steps of measuring the surface state of the carbon film by the kinetic energy of photoelectrons emitted in real time from the carbon-coated bare fiber surface and adjusting the carbon coating process parameters according to the real-time measurement feedback to achieve real-time online regulation of the surface state of the carbon film are as follows: Determine the difference in photoelectron escape kinetic energy according to the carbon film surface component-photoelectron escape kinetic energy mapping table and the photoelectron escape kinetic energy generated in real time by the carbon-coated bare fiber; Determine the change in carbon-chlorine flow rate according to the ratio of the difference in photoelectron escape kinetic energy to the ideal photoelectron escape kinetic energy value in the mapping table; Determine the feed amount of the carbon-chlorine mixed raw material according to the change amount and initial value of the carbon-chlorine flow rate; The carbon film coating of the optical fiber is carried out according to the feeding amount of the carbon-chlorine mixed raw material, thereby realizing the feedback control of the surface components of the carbon film; The carbon film surface component-photoelectron escape kinetic energy mapping table is constructed according to the ideal carbon layer surface component parameters and the ideal photoelectron escape kinetic energy value.
6. A device for manufacturing a carbon-coated optical fiber, characterized in that: include: A wire drawing device (1), a reaction chamber (2), a carbon coating and measurement feedback system (3) and a coating curing device (4); The wire drawing device (1) is used to draw the preform rod into a bare optical fiber; The raw materials required for the carbon coating process are introduced into the reaction chamber (2), and a carbon coating reaction occurs with the bare optical fiber in the reaction chamber (2); The carbon coating and measurement feedback system (3) is used to provide a laser beam irradiated on the carbon coated bare fiber, measure the thickness of the carbon film on the surface of the carbon coated bare fiber in real time through the laser light energy absorbed by the carbon coated bare fiber, and adjust the carbon coating process parameters according to the real-time measurement value feedback to achieve real-time online regulation of the carbon film thickness; The coating and curing device (4) is used for coating resin on the outside of the carbon coating layer and curing it to obtain a carbon-coated optical fiber.
7. The manufacturing device according to claim 6, characterized in that: The carbon coating and measurement feedback system (3) comprises: a thickness measurement unit (31), a thickness feedback unit (32), a hydrocarbon raw material gas cabinet (33), a carbon chlorine raw material gas cabinet (34), a first flow controller (35), a second flow controller (36) and a gas mixing device (37); The thickness measuring unit (31) is used to measure the thickness of the carbon film on the surface of the carbon-coated bare fiber in real time through the laser light energy absorbed by the carbon-coated bare fiber; The thickness feedback unit (32) is used to determine the light energy difference according to the carbon film thickness-carbon film absorption light energy mapping table and the laser light energy absorbed by the carbon-coated bare fiber in real time, and to determine the amount of electricity change of the hydrocarbon flow controller according to the ratio of the light energy difference to the ideal energy value in the mapping table; The first flow controller (35) is used to determine the feed amount of the hydrocarbon mixed raw material according to the amount of electricity change and the initial value of the hydrocarbon flow controller; The hydrocarbon raw material gas cabinet (33) is used to store hydrocarbon raw materials; The carbon-chlorine raw material gas cabinet (34) is used to store carbon-chlorine compound raw materials; The second flow controller (36) is used to control the carbon chlorine compound required for carbon coating to be supplied at a set flow rate; The gas mixing device (37) is used for premixing hydrocarbons and carbon-chlorine compounds before they enter the reaction chamber (2) to ensure that the raw materials are mixed evenly in the reaction chamber.
8. The manufacturing device according to claim 7, characterized in that: The thickness measuring unit (31) comprises: a laser diode light source, a light intensity monitor, a light filter and a photoelectric detector; The laser diode light source is used to emit a first laser beam with directivity and straightness and irradiate the carbon-coated bare fiber from one side; The light intensity monitor is used to monitor the real-time value and transmission stability of the light intensity of the first laser beam; The optical filter is arranged on the other side of the carbon-coated bare fiber, and is used to filter the influence of other light on the measurement process, and only passes the parallel light from the laser diode light source on the parallel path of the original laser; The photoelectric detector is used to receive the second laser beam emitted by the optical filter and determine the real-time value of the light intensity of the second laser beam; obtain the light energy absorbed by the carbon film by comparing the light energy of the second laser beam with the light energy of the first laser beam, and then determine the thickness of the carbon coating according to the light energy absorbed by the carbon film; or The thickness measuring unit (31) comprises: a first laser diode light source, a first light intensity monitor, a first light filter, a first photoelectric detector, a second laser diode light source, a second light intensity monitor, a second light filter and a second photoelectric detector; The first laser diode light source emits a first laser beam having directivity and straightness and irradiates the carbon-coated bare fiber from a first direction; The second laser diode light source emits a second laser beam with directivity and straightness and irradiates the carbon-coated bare fiber from a second direction; the second direction is perpendicular to the first direction; The first light intensity monitor is used to monitor the real-time value and transmission stability of the light intensity of the first laser beam; The second light intensity monitor is used to monitor the real-time value and transmission stability of the light intensity of the second laser beam; The first optical filter and the first photodetector are sequentially arranged in the first direction, the first optical filter is used to filter the influence of other light on the measurement process, and only passes the parallel light from the first laser diode light source on the parallel path of the original laser; the first photodetector is used to receive the third laser beam emitted by the first optical filter, and determine the real-time value of the light intensity of the third laser beam; the light energy absorbed by the first carbon film is obtained by comparing the light energy of the third laser beam with that of the first laser beam; The second optical filter and the second photodetector are sequentially arranged in the second direction, the second optical filter is used to filter the influence of other light on the measurement process, and only passes the parallel light from the second laser diode light source on the parallel path of the original laser; the second photodetector is used to receive the fourth laser beam emitted by the second optical filter, and determine the real-time value of the light intensity of the fourth laser beam; the light energy absorbed by the second carbon film is obtained by comparing the light energy of the fourth laser beam with the light energy of the second laser beam, and then the thickness of the carbon coating is determined according to the light energy absorbed by the first carbon film and the light energy absorbed by the second carbon film; or The thickness measuring unit (31) comprises: a laser diode light source (310), a laser beam expander (311), a laser beam splitter (312), a light intensity monitor (313), a first refractor (314), a second refractor (315), a first optical filter (316), a first photodetector (317), a second optical filter (318) and a second photodetector (319); The laser diode light source (310) is used to provide a laser beam with directivity and straightness; The laser beam expander (311) is used to expand the laser beam; The laser beam splitter (312) is used to split the expanded laser beam into two mutually perpendicular straight laser beams with equal energy, and monitor the real-time value of the light intensity and the transmission stability through the light intensity monitor (313); the two laser beams are respectively refracted vertically through the first refractor (314) and the second refractor (315), and the two laser beams remain perpendicular to each other after refraction; the two laser beams are emitted to the carbon-coated bare fiber according to the optical path and pass through to the other side of the incident optical path, and on the other side, the two laser beams are respectively passed through the first optical filter (316) and the second optical filter (318), the main function of the optical filter is to filter the influence of other light on the measurement process, and only pass the parallel light from the laser diode light source (310) on the parallel path of the original laser; the two perpendicular laser beams are respectively received by the first photodetector (317) and the second photodetector (319), and the real-time value of the light intensity is determined; by comparing with the light energy after the laser beam expansion, the carbon film absorbs the light energy; and the coating thickness is determined according to the carbon film absorbs the light energy.
9. The manufacturing device according to claim 6, characterized in that: The carbon coating and measurement feedback system (3) is also used to provide X-rays irradiated on the carbon coated bare fiber, measure the surface state of the carbon film through the kinetic energy of photoelectrons emitted in real time from the surface of the carbon coated bare fiber, and adjust the carbon coating process parameters according to the real-time measurement value feedback, so as to realize real-time online regulation of the surface state of the carbon film; The carbon coating and measurement feedback system (3) further comprises: a surface state measurement unit (38) and a surface state feedback unit (39); The surface state measuring unit (38) is used to measure the surface state of the carbon film; The surface state feedback unit (39) compares the physical quantity used to characterize the surface state of the carbon film with the surface state process setting quantity, and transmits the comparison difference to the second flow controller (36).
10. The manufacturing device according to claim 9, characterized in that: The surface state measurement unit (38) includes an X-ray source (381) and an electron energy analyzer (382); The X-ray source (381) is used to emit X-rays. When the X-rays irradiate the surface of the carbon-coated bare fiber, they interact with the surface atoms. When the photon energy is greater than the binding energy of the electrons outside the nucleus, photoelectrons can be excited. The electron energy analyzer (382) is used to measure the energy distribution of the photoelectrons passing through, and compare the photoelectron escape kinetic energy value with the surface state process setting value, and when the surface state of the carbon layer is consistent with the process, obtain the photoelectron escape kinetic energy value used to characterize the surface state of the carbon layer.